Ferrocement water tanks and their construction - Watt, S. B. (Simon B.) (Intermediate Technology Publications, 1978)
Describes how cylindrical water storage tanks of up to 150 cubic meter capacity can be built using wire-reinforced cement-mortar. Covers design and planning; costs; standard, recommended and alternative construction methods, and other information.